2021
DOI: 10.3389/fphar.2021.783641
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Protective Effects of Plant Polysaccharides: A Review

Abstract: Cardiovascular disease is a kind of heart, brain, and blood vessel injury disease by the interaction of various pathological factors. The pathogenesis of cardiovascular disease is complex with various risk factors, including abnormally elevated blood pressure, glucose, and lipid metabolism disorders, atherosclerosis, thrombosis, etc. Plant polysaccharides are a special class of natural products derived from plant resources, which have the characteristics of wide sources, diverse biological activities, and low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Polysaccharide is a natural biological macromolecule with a wide range of biological activities such as immunomodulatory, antitumor, antiviral, antioxidant, hypoglycemic, and hypolipidemic. Polysaccharides could regulate glucose and lipid metabolism by protecting islet cells, improving insulin sensitivity, regulating intestinal flora, increasing antioxidant capacity, and regulating the activity of key enzymes for glucose and lipid metabolism [38,39] .…”
Section: Polysaccharidesmentioning
confidence: 99%
“…Polysaccharide is a natural biological macromolecule with a wide range of biological activities such as immunomodulatory, antitumor, antiviral, antioxidant, hypoglycemic, and hypolipidemic. Polysaccharides could regulate glucose and lipid metabolism by protecting islet cells, improving insulin sensitivity, regulating intestinal flora, increasing antioxidant capacity, and regulating the activity of key enzymes for glucose and lipid metabolism [38,39] .…”
Section: Polysaccharidesmentioning
confidence: 99%
“…In recent years, plant polysaccharides as a class of natural products have been the subject of intensive investigation. Numerous studies have demonstrated that plant polysaccharides could improve cardiovascular diseases by anti-oxidative stress, restoring the metabolism of biological macromolecules, regulating apoptosis, and inhibiting inflammatory signal pathways (Dong et al, 2021;Zhou et al, 2021). In particular, polysaccharides have a good role in the prevention and treatment of DCM.…”
Section: Pp Alleviated Myocardial Fibrosis In Model Ratsmentioning
confidence: 99%
“…Polysaccharides are widely distributed as natural ingredients in vegetables and fruits. Several studies have shown that the polysaccharides improve cardiovascular diseases through various mechanisms, such as anti-oxidative stress, regulating metabolism, anti-inflammatory, anti-cancer, and immunity-booster properties ( 262 ).…”
Section: Cardioprotective Phytochemicals Attenuating Myocardial I/r I...mentioning
confidence: 99%